Validation of new equipment for SARS-CoV-2 diagnosis in Ecuador: Detection of the virus and antibodies generated by disease and vaccines with one POC device - Stephany D. Villota; Eliana Veloz-Villavicencio; Santiago Garcia-Iturralde; Johanna Valentina Arévalo; Suying Lu; Katariina Jaenes; Yuxiu Guo; Seray Cicek; Karen Colwill; Anne-Claude Gingras; Rod Bremner; Patricio Ponce; et al. (PLoS ONE, 2025)
The COVID-19 pandemic underscored the critical need to enhance screening capabilities and streamline diagnosis. Point-of-care (POC) tests offer a promising solution by decentralizing testing. We aimed to validate the PLUM device (LSK Technologies Inc.), a portable optical reader, to detect SARS-CoV-2 RNA using direct RT-LAMP targeting the ORF1a and E1 genes and patient antibodies by ELISA. The direct RT-LAMP assays employ nasopharyngeal swabs and bypass RNA extraction protocols through a brief chemical and physical lysis step. Test sensitivity and specificity were assessed against gold-standard detection methods in laboratory and field conditions. For samples with Ct values below 25, direct RT-LAMP showed 83% sensitivity and 90% specificity under laboratory conditions and 91% sensitivity and 92% specificity under field conditions. The nucleocapsid antigen antibody assay had 99% positive percent agreement (PPA) and 97% negative percent agreement (NPA), outperforming spike-RBD antigen (98% PPA, 92% NPA) and seroprevalence (98% PPA, 88% NPA) under laboratory conditions. Under field conditions, similar results were found for antibody detection for the nucleocapsid antigen (93% PPA; 100% NPA), spike-RBD (100% PPA; 94% NPA), and seroprevalence (90% PPA; 94% NPA). This study validated the PLUM device as a dual POC tool for direct RT-LAMP-based SARS-CoV-2 and ELISA-based COVID-19 antibody detection.